Successful early application of extracorporeal membrane oxygenation to support cardiopulmonary resuscitation for a patient suffering from severe malignant hyperthermia and cardiac arrest: a case report - Huh, Hyub (Korean J Anesthesiol, 2017)
Malignant hyperthermia (MH) may lead to metabolic crisis of skeletal muscle in susceptible individuals following exposure to triggering agents such as volatile anesthetics or depolarizing muscle relaxants. MH is a rare and a potentially lethal disease, which can lead to cardiac arrest. We report a case of severe MH, in which the rapidly evolving signs of hypermetabolism eventually resulted in cardiac arrest. Despite conventional treatments following cardiopulmonary resuscitation, the patient's vital signs did not improve. Therefore, we applied extracorporeal membrane oxygenation for providing hemodynamic support.